Prevalence of Anxiety Symptoms and Their Association With Loss Experience in a Large Cohort Sample of the Oldest-Old. Results of the AgeCoDe/AgeQualiDe Study - Welzel, Franziska D.; Stein, Janine; Röhr, Susanne; Fuchs, Angela; Pentzek, Michael; Mösch, Edelgard; Bickel, Horst; Weyerer, Siegfried; Werle, Jochen; Wiese, Birgitt; Oey, Anke; Hajek, André; et al. (Frontiers in Psychiatry, 2019)
Background: Anxiety in adults is a common mental health problem. However, studies on anxiety in the oldest-old are lacking. We sought to identify the age and gender specific prevalence of anxiety symptoms in a large sample of general practice patients. Furthermore, we investigated relevant associations of anxiety specifically with respect to recent experience of loss. Methods: Based on the German study on Ageing, Cognition and Dementia in general practice patients, a sample of 897 patients aged 82 years and older was assessed. Anxiety was assessed using the short form of the Geriatric Anxiety Inventory (GAI-SF). For the assessment of loss patients were asked whether there were cases of death in their closer social environment since the last assessment. Descriptive and logistic regression analyses were run. Results: 14.5% (95%-CI 12.4-16.8) of the oldest-old individuals (aged 82+ years, mean age: 86.8) suffered from anxiety symptoms. Highest prevalence rates were found for 82 to 85 year old women (17.2%, 95%-CI 12.6-22.1) and for 86 to 90 year old patients (both sexes) in general (15.9%, 95%-CI 12.6-19.2). Older individuals who experienced cases of death in their close social environment within the last 18 months had almost twice the odds (OR: 1.91, 95% CI 1.15 – 3.17) of reporting anxiety compared to those without a recent loss. As expected, depression and impaired cognitive status were associated with presence of anxiety symptoms. No relation was found between social network, gender, age, frailty or physical illness and anxiety in regression analysis. Conclusions: This study for the first time provides age- and gender-specific prevalence rates of anxiety symptoms and associated risk factors among a large population-based sample of oldest-old primary care attenders. Anxiety is highly prevalent in individuals aged 82 years and older. Depression, impaired cognitive status and recent experience of loss are associated with late life anxiety. Our findings support the idea that recent experience of loss should be taken seriously in the context of clinical practice with respect to diagnosing and treating anxiety in old age.